Pengaruh Beban Kerja, dan Kepribadian Terhadap Kepatuhan Kerja di PT. Pindo Deli Pulp and Paper Mills 1 - Bintang Dwi Cahya; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to identify the partial and joint impact of workload and personality on the level of work compliance at PT Pindo Deli Pulp and Paper Mills 1. The analysis method used is multiple linear regression using spss26 calculations. This population is employees of PT Pindo Deli Pulp and Paper Mills 1 with a total of 350 people using the slovin formula with a level of 5%, namely 187 respondents, This sampling applies to test validity, reliability, correlation, and hypotheses with the t test (partial) and F test (simultaneous). The results showed that there was a partial impact of workload on work compliance with a value of 2.086 quite high category,, 2) personality on work compliance with a value of 2.510 kstegori quite high 3). Together, work discipline and work environment also affect the level of work compliance, with a calculated F value of 21.581, which is significant (exceeding the critical value of 3.04). The combined effect of workload and personality on work compliance at PT Pindo Deli Pulp and Paper Mills 1 reached 19.0%.